Toxicological Study of Malic acid-Phthalic acid-Propane- 1,2-diol Copolyester (Journal of Agriculture & Rural Development, 2008)
Malic acid-phthalic acid-propane 1,2-diol copolyester (MPPC) was administered intraperitoneally to the rats at a dose of 300 Î¼g rat-1day-1 for 21 consecutive days to find out its harmful effect on rats. The gross general observations such as changes of body weight, hematological profiles, biochemical parameters of blood and the histopathology of liver, kidney, heart, lungs and spleen were investigated in control and experimental rats. The body weights of the rats were slightly increased. The changes of hematological and biochemical parameters were statistically insignificant. No abnormalities were found in the histopathology of the liver, kidney, heart, lung and spleen in the experimental group of rats when compared with control group of rats. From this study, it was inferred that malic acid- phthalic acid-propane 1,2-diol copolyester would be used as a matrix for controlled and sustained release of drugs. Key words: Malic acid-phthalic acid-propane 1,2-diol copolyester, sub-acute toxicity, haematological parameter, biochemical parameter, histopathology. DOI = 10.3329/jard.v5i1.1472 J Agric Rural Dev 5(1&2), 150-156, June 2007